O anel de GREEN da álgebra de TAFT - Pedrotti, Juliana Borges (2019)
The aim of this work is to characterize the Green ring of Taft algebra, denoted by (), where is a positive integer greater than 1 and is a primitive root of unity of order . The Green ring, denoted by (()), is generated by the isomorphism classes [] of finite dimensional ()-modules with addition given by [] + [] = [ ⊕ ] and multiplication given by the tensor product and it has a -basis given by the classes of isomorphisms of indecomposable finite dimensional ()-modules. In this work we describe the indecomposable ()-modules and the tensorial product between these. From that we show that (()) is a commutative ring generated by two elements subject to certain relations.